Study on the Principle of Cost Calculation and Economy of Steel Screw Anchors - Gan, Jingshuang; Li, Lingyun (Transactions on Economics, Business and Management Research, 2024)
With the popularization of mechanized construction of transmission line engineering and the improvement of environmental water protection requirements, some new foundations have been popularized, and have great advantages. The steel spiral anchor foundation has the advantages of short construction period, quick mechanization construction speed, and zero concrete and zero earthwork construction. According to the construction process and test requirements of steel screw anchor, the principle of calculating the construction and test cost of steel screw anchor is put forward, the economic critical point of steel screw anchor is obtained.